2016
DOI: 10.1002/stc.1900
|View full text |Cite
|
Sign up to set email alerts
|

Field monitoring and numerical simulation of the thermal actions of a supertall structure

Abstract: Structural temperature is an important loading that must be considered during the design, construction, and safety assessment. The thermal action of supertall structures has rarely been investigated because of insufficient real measurement data, as compared with that on bridges. In this study, the thermal action of the 600-m-tall Canton Tower is investigated on the basis of the comprehensive long-term SHM system installed on the structure and the numerical simulation. First, the temperature model of the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…For example, the in-construction monitoring of the Burj Khalifa tower ensured the construction accuracy of the structure during the construction through surveying and elevation compensation. 30 The long-term temperature data of the Canton Tower 110 shorten the gap in the Chinese design code regarding the temperature loading of supertall structures. 95 Field measurements of the wind effects on a 420-m-tall supertall building in Hong Kong verified the wind characteristics used in the wind-tunnel testing and FE analysis, and the wind-resistant design of high-rise structures.…”
Section: Challenges Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the in-construction monitoring of the Burj Khalifa tower ensured the construction accuracy of the structure during the construction through surveying and elevation compensation. 30 The long-term temperature data of the Canton Tower 110 shorten the gap in the Chinese design code regarding the temperature loading of supertall structures. 95 Field measurements of the wind effects on a 420-m-tall supertall building in Hong Kong verified the wind characteristics used in the wind-tunnel testing and FE analysis, and the wind-resistant design of high-rise structures.…”
Section: Challenges Discussion and Conclusionmentioning
confidence: 99%
“…(iii) The internal forces of the highest stories were larger than those of the lower stories, which is different from the wind loading effect that generally F I G U R E 6 Temperature-induced responses of Canton Tower. 110 causes the largest force in the bottom of the structure. This study provided first-hand data for the design of supertall structures in the tropical region of China.…”
Section: Temperature-induced Deflection and Stressmentioning
confidence: 99%
“…The temperature data of sections 3 and 8 are selected because they represent levels with and without functional floors, respectively. Su et al (2017a) showed that the temperature measured by the thermistors inside the CFT columns could be considered the effective temperature of the composite section of the column. In section 3, the averaged temperature of the inward and outward surfaces of the CFT columns is used as no thermistor was installed inside the CFT columns in the section.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Ni et al (2011) developed monitoring-based temperature distribution models of Guangzhou Tower in order to serve as a reliable input for numerical simulation of the temperature-induced deformations. Su et al (2017a) inputted the structural temperature of the 600-m-tall Canton Tower into an FE model of the global structure and calculated the temperature-induced deformation. They then used the model to separate the typhoon-induced quasi-static responses from the measured displacement (Su et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…10 On the one hand, the real geographical environment, terrain roughness, structural shape, and so forth are considered by SHM system, which ensures the reliability of the data. 11 On the other hand, the data can be collected in real time by SHM system, which achieves the integrity of the data. 12 Rubert et al 13 found a strategy to underpin a long-term wind farm lifetime based on SHM.…”
Section: Introductionmentioning
confidence: 99%